Combating drought in southern Africa : from relief to resilience - Prasanna, B. M.; Thierfelder, Christian; Cairns, Jill E. (2017)
Keywords: openalex:import

Managing vulnerability to drought and enhancing livelihood resilience in sub-Saharan Africa: Technological, institutional and policy options - Shiferaw, Bekele; Tesfaye, Kindie; Kassie, Menale; Abate, Tsedeke; Prasanna, B. M.; Menkir, Abebe (Weather and Climate Extremes, 2014)
Agriculture and the economies of Sub-Saharan Africa (SSA) are highly sensitive to climatic variability. Drought, in particular, represents one of the most important natural factors contributing to malnutrition and famine in many parts of the region. The overall impact of drought on a given country/region and its ability to recover from the resulting social, economic and environmental impacts depends on several factors. The economic, social and environmental impacts of drought are huge in SSA and the national costs and losses incurred threaten to undermine the wider economic and development gains made in the last few decades in the region. There is an urgent need to reduce the vulnerability of countries to climate variability and to the threats posed by climate change. This paper attempts to highlight the challenges of drought in SSA and reviews the current drought risk management strategies, especially the promising technological and policy options for managing drought risks to protect livelihoods and reduce vulnerability. The review suggests the possibilities of several ex ante and ex post drought management strategies in SSA although their effectiveness depends on agro-climatic and socio-economic conditions. Existing technological, policy and institutional risk management measures need to be strengthened and integrated to manage drought ex ante and to minimize the ex post negative effects for vulnerable households and regions. A proactive approach that combines promising technological, institutional and policy solutions to manage the risks within vulnerable communities implemented by institutions operating at different levels (community, sub-national, and national) is considered to be the way forward for managing drought and climate variability.
Keywords: openalex:import

Adapting maize production to climate change in sub-Saharan Africa - Cairns, Jill E.; Hellin, Jon; Sonder, Kai; Araus, José Luís; MacRobert, John; Thierfelder, Christian; Prasanna, B. M. (Food Security, 2013)
Given the accumulating evidence of climate change in sub-Saharan Africa, there is an urgent need to develop more climate resilient maize systems. Adaptation strategies to climate change in maize systems in sub-Saharan Africa are likely to include improved germplasm with tolerance to drought and heat stress and improved management practices. Adapting maize systems to future climates requires the ability to accurately predict future climate scenarios in order to determine agricultural responses to climate change and set priorities for adaptation strategies. Here we review the projected climate change scenarios for Africa’s maize growing regions using the outputs of 19 global climate models. By 2050, air temperatures are expected to increase throughout maize mega- environments within sub-Saharan Africa by an average of 2.1°C. Rainfall changes during the maize growing season varied with location. Given the time lag between the development of improved cultivars until the seed is in the hands of farmers and adoption of new management practices, there is an urgent need to prioritise research strategies on climate change resilient germplasm development to offset the predicted yield declines.
Keywords: openalex:import

Adapting maize production to climate change in sub-Saharan Africa - Cairns, Jill E.; Hellin, Jon; Sonder, Kai; Araus, José Luís; MacRobert, John; Thierfelder, Christian; Prasanna, B. M. (Food Security, 2013)
Given the accumulating evidence of climate change in sub-Saharan Africa, there is an urgent need to develop more climate resilient maize systems. Adaptation strategies to climate change in maize systems in sub-Saharan Africa are likely to include improved germplasm with tolerance to drought and heat stress and improved management practices. Adapting maize systems to future climates requires the ability to accurately predict future climate scenarios in order to determine agricultural responses to climate change and set priorities for adaptation strategies. Here we review the projected climate change scenarios for Africa’s maize growing regions using the outputs of 19 global climate models. By 2050, air temperatures are expected to increase throughout maize mega- environments within sub-Saharan Africa by an average of 2.1°C. Rainfall changes during the maize growing season varied with location. Given the time lag between the development of improved cultivars until the seed is in the hands of farmers and adoption of new management practices, there is an urgent need to prioritise research strategies on climate change resilient germplasm development to offset the predicted yield declines.
Keywords: openalex:import

Adapting maize production to climate change in sub-Saharan Africa - Cairns, Jill E.; Hellin, Jon; Sonder, Kai; Araus, José Luís; MacRobert, John; Thierfelder, Christian; Prasanna, B. M. (Food Security, 2013)
Given the accumulating evidence of climate change in sub-Saharan Africa, there is an urgent need to develop more climate resilient maize systems. Adaptation strategies to climate change in maize systems in sub-Saharan Africa are likely to include improved germplasm with tolerance to drought and heat stress and improved management practices. Adapting maize systems to future climates requires the ability to accurately predict future climate scenarios in order to determine agricultural responses to climate change and set priorities for adaptation strategies. Here we review the projected climate change scenarios for Africa’s maize growing regions using the outputs of 19 global climate models. By 2050, air temperatures are expected to increase throughout maize mega- environments within sub-Saharan Africa by an average of 2.1°C. Rainfall changes during the maize growing season varied with location. Given the time lag between the development of improved cultivars until the seed is in the hands of farmers and adoption of new management practices, there is an urgent need to prioritise research strategies on climate change resilient germplasm development to offset the predicted yield declines.
Keywords: openalex:import

Adapting maize production to climate change in sub-Saharan Africa - Cairns, Jill E.; Hellin, Jon; Sonder, Kai; Araus, José Luís; MacRobert, John; Thierfelder, Christian; Prasanna, B. M. (Food Security, 2013)
Given the accumulating evidence of climate change in sub-Saharan Africa, there is an urgent need to develop more climate resilient maize systems. Adaptation strategies to climate change in maize systems in sub-Saharan Africa are likely to include improved germplasm with tolerance to drought and heat stress and improved management practices. Adapting maize systems to future climates requires the ability to accurately predict future climate scenarios in order to determine agricultural responses to climate change and set priorities for adaptation strategies. Here we review the projected climate change scenarios for Africa’s maize growing regions using the outputs of 19 global climate models. By 2050, air temperatures are expected to increase throughout maize mega- environments within sub-Saharan Africa by an average of 2.1°C. Rainfall changes during the maize growing season varied with location. Given the time lag between the development of improved cultivars until the seed is in the hands of farmers and adoption of new management practices, there is an urgent need to prioritise research strategies on climate change resilient germplasm development to offset the predicted yield declines.
Keywords: openalex:import; openalex:yes

Adapting maize production to climate change in sub-Saharan Africa - Cairns, Jill E.; Hellin, Jon; Sonder, Kai; Araus, José Luís; MacRobert, John; Thierfelder, Christian; Prasanna, B. M. (Food Security, 2013)
Given the accumulating evidence of climate change in sub-Saharan Africa, there is an urgent need to develop more climate resilient maize systems. Adaptation strategies to climate change in maize systems in sub-Saharan Africa are likely to include improved germplasm with tolerance to drought and heat stress and improved management practices. Adapting maize systems to future climates requires the ability to accurately predict future climate scenarios in order to determine agricultural responses to climate change and set priorities for adaptation strategies. Here we review the projected climate change scenarios for Africa’s maize growing regions using the outputs of 19 global climate models. By 2050, air temperatures are expected to increase throughout maize mega- environments within sub-Saharan Africa by an average of 2.1°C. Rainfall changes during the maize growing season varied with location. Given the time lag between the development of improved cultivars until the seed is in the hands of farmers and adoption of new management practices, there is an urgent need to prioritise research strategies on climate change resilient germplasm development to offset the predicted yield declines.
Keywords: openalex:import; openalex:yes

Adapting maize production to climate change in sub-Saharan Africa - Cairns, Jill E.; Hellin, Jon; Sonder, Kai; Araus, José Luís; MacRobert, John; Thierfelder, Christian; Prasanna, B. M. (Food Security, 2013)
Given the accumulating evidence of climate change in sub-Saharan Africa, there is an urgent need to develop more climate resilient maize systems. Adaptation strategies to climate change in maize systems in sub-Saharan Africa are likely to include improved germplasm with tolerance to drought and heat stress and improved management practices. Adapting maize systems to future climates requires the ability to accurately predict future climate scenarios in order to determine agricultural responses to climate change and set priorities for adaptation strategies. Here we review the projected climate change scenarios for Africa’s maize growing regions using the outputs of 19 global climate models. By 2050, air temperatures are expected to increase throughout maize mega- environments within sub-Saharan Africa by an average of 2.1°C. Rainfall changes during the maize growing season varied with location. Given the time lag between the development of improved cultivars until the seed is in the hands of farmers and adoption of new management practices, there is an urgent need to prioritise research strategies on climate change resilient germplasm development to offset the predicted yield declines.
Keywords: openalex:import

Climate change and maize production in Zimbabwe - Cairns, Jill E.; Magorokosho, Cosmos; Olsen, M. W.; Sonder, Kai; Stirling, Clare M.; Zaman‐Allah, Mainassara; Prasanna, B. M.; Fantaye, Kindie Tesfaye (2016)
Keywords: openalex:import

Meeting the challenges of global climate change and food security through innovative maize research. Proceedings of the 3rd National Maize Workshop of Ethiopia, Addis Ababa, Ethiopia, 18-20 April, 2011. - Worku, Mitiku Adisu; Twumasi-Afriyie, S.; Wolde, Legesse; Tadesse, Bedassa; Demisie, G.; Bogale, G.; Wegary, Dagne; Prasanna, B. M. (2012)
Keywords: openalex:import

Developing maize varieties that adapt to climate change :the role of CIMMYT and partners in Africa - Worku, Mitiku Adisu; Mugo, Stephen; Beyene, Yoseph; Makumbi, Dan; Owino, F.; Abate, Tsedeke; Olsen, M.; Machida, L.; Suresh, Lavanya; Prasanna, B. M.; Jumbo, M.B. (2016)
Keywords: openalex:import

Molecular Breeding for Drought Tolerant Maize in Sub Saharan Africa. - Semagn, Kassa; Beyene, Yoseph; Nair, Sudha; Babu, Raman; Magorokosho, Cosmos; Tarekegne, Amsal; Mugo, Stephen; Meisel, Barbara; Sehabiague, Pierre; Makumbi, Dan; Atlin, G. N.; Warburton, Marilyn L.; et al. (2013)
Keywords: openalex:import